Natural product synthesis at the interface of chemistry and biology - Hong, Jiyong (2014)
Nature has evolved to produce unique and diverse natural products that possess high target affinity and specificity. Natural products have been the richest sources for novel modulators of biomolecular function. Since the chemical synthesis of urea by Wöhler, organic chemists have been intrigued by natural products, leading to the evolution of the field of natural product synthesis over the past two centuries. Natural product synthesis has enabled natural products to play an essential role in drug discovery and chemical biology. With the introduction of novel, innovative concepts and strategies for synthetic efficiency, natural product synthesis in the 21st century is well poised to address the challenges and complexities faced by natural product chemistry and will remain essential to progress in biomedical sciences.